2009
DOI: 10.1111/j.1365-2702.2008.02652.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of the effects of cryotherapy on pain, eyelid oedema and facial ecchymosis after craniotomy

Abstract: Aim. To identify the effects of cryotherapy on patient discomfort following craniotomy. Background. Following craniotomy, many patients suffer from unexpected discomfort, including pain, eyelid oedema and ecchymosis. Cryotherapy is regarded as a safe method for managing these postcraniotomy problems. Design. Randomised controlled trial. Methods. A total of 97 Korean patients who underwent elective supratentorial craniotomy were randomly assigned to a cryotherapy or a control group. In the cryotherapy group, ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
1
31
0
3
Order By: Relevance
“…3 The neural effects are also thought to be mediated through vasoconstriction, leading to decreased edema, decreased release of localized pain mediators, and a slowing of nerve conduction velocity of peripheral nerve fibers. 8 Our study of upper blepharoplasty shows no treatment effect of cooling on edema, erythema, and hematoma. In gynecologic patients undergoing exploratory laparotomy, cold ice pack application did not improve postoperative pain, 5 nor did cooling with facial ice packs improve postoperative pain, facial swelling, or trismus after third molar surgery.…”
Section: Discussionmentioning
confidence: 60%
“…3 The neural effects are also thought to be mediated through vasoconstriction, leading to decreased edema, decreased release of localized pain mediators, and a slowing of nerve conduction velocity of peripheral nerve fibers. 8 Our study of upper blepharoplasty shows no treatment effect of cooling on edema, erythema, and hematoma. In gynecologic patients undergoing exploratory laparotomy, cold ice pack application did not improve postoperative pain, 5 nor did cooling with facial ice packs improve postoperative pain, facial swelling, or trismus after third molar surgery.…”
Section: Discussionmentioning
confidence: 60%
“…Results indicated no appreciable difference in the intensity of ecchymosis between the postoperative hypothermia group and the control group, although significantly less ecchymosis was reported in the group receiving operative and postoperative hypothermia . Similar results by Shin and colleagues supporting early application of a cold compress was found in postcraniotomy patients . These findings suggest that the timing and duration of cold compress therapy is related to its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, therapy was initiated immediately after bruise induction, and the treatment period lasted 10 minutes. Shehadi treated participants throughout surgery and continuously during waking hours for 2 days, and Shin and colleagues treated patients for 20 minutes per waking hour for 3 days after surgery . In Shehadi's study, there was no difference from control in bruise reduction in participants who received only postoperative cryotherapy, whereas participants in the study by Shin and colleagues, who underwent similar treatment, showed significantly less ecchymosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this procedure presents a risk of infectious complications and an increase in surgical costs. On the other hand, the eyelid edema harms patients' vision, (1) causes pain, hampers eye hygiene and sometimes results in restlessness.…”
Section: %mentioning
confidence: 99%
“…(1) The incidence of subgaleal collection can vary from 7% to 33%, and periorbital edema from 2.8% to 100%. (2,3) During the immediate postoperative period of craniotomy, patients can have neurosurgery complications, such as hematomas and cerebral edema as a result of surgical trauma.…”
Section: Introductionmentioning
confidence: 99%